2018
DOI: 10.1371/journal.ppat.1007296
|View full text |Cite
|
Sign up to set email alerts
|

The papain-like protease determines a virulence trait that varies among members of the SARS-coronavirus species

Abstract: SARS-coronavirus (CoV) is a zoonotic agent derived from rhinolophid bats, in which a plethora of SARS-related, conspecific viral lineages exist. Whereas the variability of virulence among reservoir-borne viruses is unknown, it is generally assumed that the emergence of epidemic viruses from animal reservoirs requires human adaptation. To understand the influence of a viral factor in relation to interspecies spillover, we studied the papain-like protease (PLP) of SARS-CoV. This key enzyme drives the early stage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
67
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(70 citation statements)
references
References 70 publications
3
67
0
Order By: Relevance
“…This includes five PLPeISG15 complex structures. The SARS-CoV PLP was among the first viral DUBs to be recognized as possessing deISGylase activity and has been associated with the reduction of ISG15 conjugates and enhanced immune suppression [41,44,45]. Similar effects were observed in the more recently emergent MERS-CoV, suggesting an association between coronavirus pathogenicity and the presence of strong deISGylating activity [46].…”
Section: Isg15 and Viral Proteinsmentioning
confidence: 85%
See 1 more Smart Citation
“…This includes five PLPeISG15 complex structures. The SARS-CoV PLP was among the first viral DUBs to be recognized as possessing deISGylase activity and has been associated with the reduction of ISG15 conjugates and enhanced immune suppression [41,44,45]. Similar effects were observed in the more recently emergent MERS-CoV, suggesting an association between coronavirus pathogenicity and the presence of strong deISGylating activity [46].…”
Section: Isg15 and Viral Proteinsmentioning
confidence: 85%
“…This provided protection against EAV infection and demonstrated the feasibility of creating viable DUB-deficient mutant recombinant viruses as vaccine candidates, though under the conditions studied it could not be established that this provided greater benefit compared to wild-type virus. Another recent achievement demonstrated a similar decoupling of activity with PLP mutants in a SARS-CoV reverse genetics system, also providing key insights into virus immune suppression and pathogenesis [44]. Regrettably, these studies focused solely on the effect of these mutants on ubiquitination.…”
Section: Current Outlook and Challenges To Evaluating The Specific Efmentioning
confidence: 97%
“…Thus concluded that there was a basic connection between the nsp3 association and the inception of coronavirus infection (Hurst et al, 2013a). Besides, they investigated that NSP3 contains the papain-like protease and is regarded as significant for SARS infection (Niemeyer et al, 2018). Variations found in subjects began from Wuhan are situated in either TM1 or Y space which is profoundly saved (Hurst et al, 2013a(Hurst et al, , 2013b.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, deISGylating activity appears to play a role in later stages of CCHFV infection. A recent study demonstrated a similar impact of DUB activity in viral immune suppression during the replication cycle of severe acute respiratory syndrome coronavirus (SARS-CoV) [31]. Specifically, when the DUB activity of the SARS-CoV papain-like protease (PLpro) was selectively disrupted, the virus showed increased sensitivity to IFN and slower growth kinetics.…”
mentioning
confidence: 95%